Parametric Study of Large Settlement Due to Prefabricated Vertical Drain with Surcharge Preloading - Mokhammad Farid Maruf (Kadiri University, 2022)
Prefabricated vertical drain (PVD) combined with preloading is one way to deal with soft soil conditions. The predicted settlement becomes the first information in designing the surcharge, PVD configuration and depth, and the time required to complete the consolidation. Prediction of consolidation settlement that using one-dimensional theory considerably underestimated the field settlement along the construction of the surcharge placement stage. This paper intends to evaluate the completed PVD preloading construction project. Inclinometer monitoring data was evaluated to confirm whether the consolidation existed on preferred clay layers. The parametric study evaluated the root cause of the gap between prediction settlement and monitoring data. The root cause analysis continued with a parametric analysis using back calculations. The back analysis involved various Cc, Cs, and pc' that play a significant role in soil settlement. The results show that the conservative value of those parameters simulated separately could not raise the ultimate settlement into inner upper and lower bond results. However, combining those would lead to more accurate predictions that agree with the ultimate settlement. This parametric analysis result also confirms that overconfidence in picking soil parameters could lead to underestimating field settlement. Furthermore, selecting conservative parameters in consolidation settlement should avoid a big gap between prediction and field ones and put construction safe. It was decisive work to be done for further anticipation during and post-construction.